(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: To describe the clinical and paraclinical characteristics of patients with stage I–IIA non-small cell lung cancer treated at Military Hospital 175 from January 2015 to December 2020. Subjects and methods: An uncontrolled intervention study on 83 patients diagnosed with stage I - IIa non-small cell lung cancer who underwent thoracoscopy at Military Hospital 175 from January 2015 to December 2020. Results: Early stage lung cancer often had symptoms of chest pain 44.6%, cough sputum 38.6%, patients often related to smoking 39/83 (47%). Preoperative diagnosis on computed tomography stage IA accounted for 52/83 (62.7%); stage IB accounted for 27/83 (32.5%); only 4 (4.8%) patients with tumor ≤ 5 cm and lymph nodes on computed tomography at stage IIA. Most of the patients had histopathology of adenocarcinoma 71/83 (85.5%); only 12/83 (14.5%) patients had squamous cell histology. Conclusion: Common lung cancer symptoms were chest pain, cough with phlegm, related to smoking. Most of the patients had histopathology of adenocarcinoma.